2022
DOI: 10.1186/s12893-022-01754-1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a perfused cadaver model for simulated trauma resuscitation in advanced surgical skills training

Abstract: Background To develop a perfused cadaveric model for trauma surgery simulation, and to evaluate its efficacy in trauma resuscitation advanced surgical skills training. Methods Fourteen fourth-year general surgery residents attended this workshop at Siriraj Hospital (Bangkok, Thailand). Inflow and outflow cannulae and a cardiopulmonary bypass pump were used to create the perfusion circuit. Inflow was achieved by cannulating the right common carotid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
0
0
Order By: Relevance
“…Our study indicated that mortality rates may have decreased with increasing proficiency in REBOA, suggesting the need for further expansion and development of structured training programs such as ET-REBOA. This would include simulationbased training and the incorporation of REBOA training into undergraduate or residency curricula, which have been shown to improve surgical skills and patient outcomes [4,[23][24][25][26]. Additionally, further investment in research is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…Our study indicated that mortality rates may have decreased with increasing proficiency in REBOA, suggesting the need for further expansion and development of structured training programs such as ET-REBOA. This would include simulationbased training and the incorporation of REBOA training into undergraduate or residency curricula, which have been shown to improve surgical skills and patient outcomes [4,[23][24][25][26]. Additionally, further investment in research is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…While ATLS is a solid foundation, there are advanced surgical courses, such as perfused cadaver courses, that could be expanded to include EPs outside of GME programs. 32,33 EPs could practice initial resuscitation/procedures and then the…”
Section: Discussionmentioning
confidence: 99%
“…Include EPs in trauma focused surgical courses. While ATLS is a solid foundation, there are advanced surgical courses, such as perfused cadaver courses, that could be expanded to include EPs outside of GME programs 32,33 . EPs could practice initial resuscitation/procedures and then the surgeon can be integrated into patient scenarios prior to proceeding to surgical exposures.…”
Section: Recommendationsmentioning
confidence: 99%